Addition of milk fat globule membrane as an ingredient of infant formulas for resembling the polar lipids of human milk. (October 2016) - Claumarchirant, Lorena; Cilla, Antonio; Matencio, Esther; Sanchez-Siles, Luis Manuel; Castro-Gomez, Pilar; Fontecha, Javier; Alegría, Amparo; Lagarda, María Jesús
Abstract: Polar lipid (PL) contents in human milk (HM) from two different geographic zones in Spain (central and coastal) were determined. These PLs were also analysed in several infant formulas (IFs), three of which contained milk fat globule membrane (MFGM), an ingredient used to resemble the PL profile of HM. Total PL in HM decreased significantly ( p  < 0.05) from transitional milk (48.62 mg 100 mL −1 ) to 6 months (28.66 mg 100 mL −1 ). In HM, sphingomyelin was the most abundant PL, followed by phosphatidylethanolamine; in IFs the most abundant PL was phosphatidylethanolamine. Only IFs with MFGM (54.79–58.07 mg 100 mL −1 ) could supply the total and individual PL content present in all lactation periods, with the exception of sphingomyelin, which did not match the content in transitional milk. PL intake by infants fed HM or IFs was determined to be 96–306 and 152–575 mg day −1, respectively.